Disease-free Survival of Patients with Differentiated Thyroid Cancer: A Study from a Tertiary Center in Oman - Fathimabeebi P. Kunjumohamed; Abdulhakeem Al Rawahi; Noor B. Al Busaidi; Hilal N. Al Musalhi (Oman Medical Journal, 2021)
Objectives: As with global trends, the prevalence of differentiated thyroid cancer (DTC) has increased in recent years in Oman. However, to the best of our knowledge, no local studies have yet been published evaluating the prognosis of DTC cases in Oman. This study aimed to assess disease-free survival (DFS) and prognostic factors related to DTC among Omani patients attending a tertiary care center. Methods: This retrospective, observational cohort study was conducted between January 2006 and May 2016 at the National Diabetes and Endocrine Center in Oman. Data related to DFS and prognostic factors were obtained from the electronic medical records of all ≥ 18-year-old patients diagnosed with DTC during the study period. Results: A total of 346 DTC cases were identified. Overall, 82.7% of patients were disease-free at their last follow-up appointment. Univariate analysis indicated that various tumor characteristics including histological subtype (i.e., papillary carcinoma, Hurthle cell cancer, and minimally invasive follicular thyroid carcinoma), lymph node status, number of lymph node metastases, distant metastasis status, and TNM status (primary tumor (T), regional lymph node (N), distant metastasis (M) stage) were strong prognostic factors for DFS (p < 0.050). According to multivariate regression analysis, lymph node status, extrathyroidal extension, and angiovascular invasion were independent predictors of DFS (p < 0.050). Conclusions: The overall prognosis of DTC among Omani patients was excellent. Treatment and follow-up strategies for patients with DTC should be tailored based on the individual’s risk factor profile.